The Role of The Intra-School Student Organization (OSIM) in Developing Critical Thinking and Emotional Intelligence: A Study at MTS Negeri 2 Sidoarjo - Muhammad Sendy Isnanda; Aprilia Mulyani (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
In today's era, teenagers must have high critical thinking abilities and emotional intelligence in the age of digital globalization since digital information spreads quickly and artificial intelligence (AI) is widely used. Data from the real world shows that an over-reliance on technology causes a crisis in digital literacy, a decrease in empathy, and an inability to control emotions. A strategic foundation for character development in the madrasah setting is provided by the Intra-Madrasah Student Organization (OSIM). The purpose of this study is to describe how the OSIM program at MTs Negeri 2 Sidoarjo fosters students critical thinking abilities in the digital age and describe how OSIM activities contribute to the development of its executive members Emotional Quotient (EQ), specifically with regard to empathy and self-control. The findings reveal that, the two main components of Emotional Quotient (EQ) empathy and self-control were proven to be strengthened through intensive social interactions within the organization. OSIM at MTs Negeri 2 Sidoarjo functions as a character-building ecosystem that integrates critical thinking and emotional intelligence simultaneously.